2018
DOI: 10.1186/s41984-018-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Inner membrane opening during the burr-hole evacuation of a chronic subdural hematoma: risk-adding or recurrence-preventing?

Abstract: Background: Chronic subdural hematoma (CSDH) is a common situation in neurosurgical practice. Only a few studies had mentioned the opening of the inner membrane during the burr-hole evacuation of a CSDH. This study was designed to assess the benefits of inner membrane opening in the burr-hole evacuation of a CSDH and to find out if there is an added risk of such step that overweighs its benefits. Methods: This is a descriptive cohort study that retrospectively reviewed 81 patients who underwent CSDH evacuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…26 For this reason, it was decided to refer to this technique as a Retrosigmoid/Para-asterional burr hole, because the description of a burr hole has an average size of a dime (approximately 17.9 mm), the same dimensions used in the patients included in the present study (18 mm). 27 TN is a high incidence pathology, and with high health costs. MVD of the trigeminal nerve is established as a therapeutic strategy, with complete resolution of symptoms and low remission in 10 years follow up 12 .…”
Section: Discussionmentioning
confidence: 99%
“…26 For this reason, it was decided to refer to this technique as a Retrosigmoid/Para-asterional burr hole, because the description of a burr hole has an average size of a dime (approximately 17.9 mm), the same dimensions used in the patients included in the present study (18 mm). 27 TN is a high incidence pathology, and with high health costs. MVD of the trigeminal nerve is established as a therapeutic strategy, with complete resolution of symptoms and low remission in 10 years follow up 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a craniectomy is not an adequate term for the procedure, because an article that evaluates the trephinations, trephines, and craniectomies found that "craniectomy" is a term used to refer to a huge cranial opening or window of variable shape that may include a size bigger than 4 cm that corresponds to the size of a trepan [27]. For this reason, it was decided to refer to this technique as a retrosigmoid parasterional burr-hole, because the description of a burr-hole has an average size of a dime (approximately 17.9 mm), the same dimensions used in the patients included in the present study (18 mm) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Elayouty et al was based on performing BHC with restricted membranectomy. The authors reported that adding membranectomy to BHC reduces the risk of recurrence [ 81 ]. Sahyouni et al conducted a meta-analysis of 17 cohort studies, showing that craniotomy with the excision of membranes is related to a lower recurrence risk but similar mortality and morbidity rates when compared to the literature rates for craniotomies without membranectomy [ 82 ].…”
Section: Discussionmentioning
confidence: 99%